h - Kulikov, Alexander; Vereshchagin, Nikolay; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the proceedings of the 6th International Computer Science Symposium in Russia, CSR 2011, held in St. Petersburg, Russia, in June 2011. The 29 papers presented were carefully reviewed and selected from 76 submissions. The scope of topics of the symposium was quite broad and covered basically all areas of the foundations of theoretical computer science.
Keywords: Computer science; Computer software; Logic design; Computational complexity; Computer Science; Algorithm Analysis and Problem Complexity; Logics and Meanings of Programs; Mathematical Logic and Formal Languages; Discrete Mathematics in Computer Science; Computation by Abstract Devices; Mathematics of Computing